UHPLC-Q-Orbitrap HRMS-based metabolomic show biological pathways involved in rice (Oryza sativa L.) under fe toxicity stress - Turhadi, Turhadi; Hamim, Hamim; Ghulamahdi, Munif; Miftahudin, Miftahudin (Penerbit Universiti Kebangsaan Malaysia, 2023)
The iron (Fe) toxicity stress is still a serious problem in rice cultivation, especially on land with high Fe content. The Fe toxicity stress affects various complex physiological aspects of plants. The metabolomic analysis using LC-MS is expected to provide information about rice’s metabolism regulation under Fe toxicity stress. The objective of this study was to show the biological pathway signature in rice after exposure to Fe toxicity stress using UHPLC-Q-Orbitrap HRMS-based metabolomic analysis. The two rice varieties, i.e., IR64 (Fe-sensitive) and Pokkali (Fe-tolerant) were analyzed their metabolites using UHPLC-Q-Orbitrap HRMS. The metabolite profiles of both varieties were analyzed using MetaboAnalyst 5.0 software. The results showed that Fe toxicity stress affected the metabolite profile in both root and shoot tissues of two rice varieties. A number of 102 metabolites were detected in root and shoot tissues of rice. The comprehensive univariate and multivariate analyses showed that 1-aminocyclopropane-1-carboxylate (ACC) in shoot tissues and galactose in root tissues was suggested as metabolite markers for Fe tolerance character of rice var. Pokkali. The genes encoded the enzymes involved in biosynthetic pathway of both metabolite markers could be a target to be explored for Fe toxicity tolerance in rice.